Effect of Paternal DNA Damage on Paternal DNA Degradation and Early Embryonic Development in Mouse Embryo: Supporting Evidence by GammaH2AX Expression - Chang Jin Kim; Kyung-Bon Lee (Journal of Animal Reproduction and Biotechnology, 2019)
This study was investigated to test whether the zygote recognized the topoisomerase II beta (TOP2B) mediated DNA fragmentation in epididymal spermatozoa or the nuclease degradation in vas deferens spermatozoa by testing for the presence of gammaH2AX (γH2AX). The γH2AX is phosphorylation of histone protein H2AX on serine 139 occurs at sites flanking DNA double-stranded breaks (DSBs). The presence of γH2AX in the pronuclei of mouse zygotes which were injected with DNA broke epididymal spermatozoa was tested by immunohistochemistry at 5 and 9 h post fertilization, respectively. Paternal pronuclei that arose from epididymal spermatozoa treated with divalent cations did not stain for γH2AX at 5 h. On the other hand, in embryos injected with vas deferences spermatozoa that had been treated with divalent cations, γH2AX was only present in paternal pronuclei, and not the maternal pronuclei at 5 h. Interestingly, both pronuclei stained positively for γH2AX for all treatments and controls at 9 h after sperm injection. In conclusion, the embryos recognize DNA that is damaged by nuclease, but not by TOP2B because H2AX in phosphorylated in paternal pronuclei resulting from spermatozoa treated with fragmented DNA from vas deferens spermatozoa treated with divalent cations, but not from epididymal spermatozoa treated the same way.